1999
DOI: 10.1021/ic980877n
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Molecular Geometry, Electronic Structure, and Thermal Stability of Phosphazene and Heterophosphazene Rings with ab Initio Molecular Orbital Calculations

Abstract: Ab initio molecular orbital calculations at the MP2/6-31G level of theory have been used to study the molecular geometry, electronic structure, and the thermal stability of six-membered phosphazene and heterophosphazene rings. The studies included the phosphazene ring [NPCl(2)](3), the carbophosphazene ring [(NCCl)(NPCl(2))(2)], and three thionylphosphazene rings [(NSOX)(NPCl(2))(2)] (X = F, Cl) and [(NSOF)(NPF(2))(2)] and their cations [(NPCl)(NPCl(2))(2)](+), [(NC)(NPCl(2))(2)](+), and [(NSO)(NPY(2))(2)](+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…4,5 Heteroatoms, such as carbon or sulfur, could be introduced into the polymers backbone resulting in polyheterophosphazenes. [6][7][8] Besides linear poly-phosphazes, star, dendritic, block copolymeric, cyclolinear, and cyclomatrix architectures have been synthesized. 9,10 A versatile building block for the preparation of materials based on phosphazenes is the cyclic phosphazene trimer hexachlorocyclotriphosphazene [NPCl 2 ]3, HCCP.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Heteroatoms, such as carbon or sulfur, could be introduced into the polymers backbone resulting in polyheterophosphazenes. [6][7][8] Besides linear poly-phosphazes, star, dendritic, block copolymeric, cyclolinear, and cyclomatrix architectures have been synthesized. 9,10 A versatile building block for the preparation of materials based on phosphazenes is the cyclic phosphazene trimer hexachlorocyclotriphosphazene [NPCl 2 ]3, HCCP.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Cyclic phosphazenes such as P 3 N 3 (OC 6 H 4 CF 3 ) 4 (OC 6 H 4 F) 2 [9] are used as additives to lubricants. [10] Simple (PNX 2 ) 3 phosphazenes (X = H, F, Cl, NH 2 ) were studied by DFT and ab initio calculations, [9,[11][12][13][14][15][16] as well as normal coordinate analyses. [17][18][19][20][21] These investigations were also sparked by the special electronic structure of the phosphazene rings.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] These investigations were also sparked by the special electronic structure of the phosphazene rings. [11,13,16,22,23] In the halogen-substituted P 3 N 3 X 6 cyclophosphazenes the basicity of the ring nitrogen atom is very low. Therefore, little is known about the complexing abilities of the P 3 N 3 X 6 halophosphazenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-phthalimidoalkanoyl substitution for 4-8 leads to smaller band gap than N-acetyl, N-ethanoyl substitution for 2 and 3 respectively, since the LUMO energy for 4-8 is lowered more than for compounds with N-acetyl, N-ethanoyl moieties 2, 3. Sella et al and Sawicka et al proposed arguments to explain the observed easier nucleophilic ring opening and cleavage reactions [8][9][10]. One can therefore identify for N-acyl-AGs 2-8 the low-lying LUMO, as a site will be most likely involved in reactions with nucleophiles.…”
Section: Resultsmentioning
confidence: 98%